К ПРОБЛЕМЕ ГРАНИЦЫ НИЖНЕГО И СРЕДНЕГО КАРБОНА В ДОНБАССЕ, ТЯНЬ-ШАНЕ И НА УРАЛЕ - Иванова Р.М.; Кулагина Е.И.; Румянцева З.С.; Лядова Р.А.; Масло А.И. (My University, 1992)
The Mid-Carboniferous boundary in the Urals and Donets Basin is situated at the bottom of Plectostaffella bogdanovkensis foraminiferal Zone. It is approximately corresponds to the base of Homoceras ammonoid Zone and appearance of the conodont genus Declinognathodus. Z.S. Rumyantzeva have been distinguished two foraminiferal zones: Plectostaffella posochovae (subzone H1) and P. bogdanovkensis (subzone H2).
Keywords: Карбон; Палеозой::Каменноугольная